Behavioural underpinning of mito-nuclear discordances: insights from fire salamanders - Andrea Chiocchio; Erica de Rysky; Claudio Carere; Giuseppe Nascetti; Roberta Bisconti; Daniele Canestrelli (Royal Society Open Science)
Mito-nuclear discordances across secondary contact zones have been described in a wide range of organisms. They consist of a spatial mismatch between nuclear and mitochondrial genomes in terms of location and extension of the contact zone between distinct evolutionary lineages. Despite the evolutionary and biogeographic causes of mito-nuclear discordances having been extensively investigated, we still lack a clear understanding of their phenotypic underpinnings. Here, we test the hypothesis that mtDNA variation could be associated with behavioural variation and that such association could contribute to asymmetric mitochondrial introgression across a secondary contact zone. We analysed behavioural variation across the mtDNA secondary contact zone of the fire salamander Salamandra salamandra in central Italy, which is displaced 600 km from the nuclear contact zone. We found distinct behavioural profiles in the two mitotypes co-occurring in the contact zone. The introgressed mitotype was associated with a ‘slow-thorough’ dispersal profile, characterized by a less active but more cautious and accurate exploration strategy. This pattern was consistent across life stages and contexts: aquatic larvae and terrestrial juveniles, spontaneous activity and response to novelty. These results support the intriguing hypothesis that personality traits associated with distinct mitotypes could contribute to differential mitochondrial introgression and the formation of biogeographic patterns of mito-nuclear discordance.